1996
DOI: 10.1002/(sici)1096-8652(199609)53:1<18::aid-ajh4>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

High dose of intravenous antithrombin III without heparin in the treatment of disseminated intravascular coagulation and organ failure in four children

Abstract: In several animal experiments, high doses of antithrombin 111 concentrates have shown beneficial effects on mortality and reversal of coagulation abnormalities which had resulted from disseminated intravascular coagulation. Other experiments have suggested that antithrombin 111 infusion without heparin is effective in the treatment of organ failure. We clinically treated children suffering disseminated intravascular coagulation only with antithrombin concentrate. Four patients suffering disseminated intravascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other studies of antithrombin substitution (113), antithrombin therapy (114), or combination therapy of antithrombin with heparin (115)(116)(117) were purely observational, with no control groups or randomization.…”
Section: Treatmentmentioning
confidence: 99%
“…Other studies of antithrombin substitution (113), antithrombin therapy (114), or combination therapy of antithrombin with heparin (115)(116)(117) were purely observational, with no control groups or randomization.…”
Section: Treatmentmentioning
confidence: 99%
“…49 ATIII is another therapeutic option that attenuates organ damage by decreasing microthrombus formation and endothelial injury. 50 In children, one uncontrolled study in four patients 20 days to 17 months showed that high-dose ATIII, without heparin, was safe and effective in treating DIC and organ failure, likely through improved organ blood flow. 50 A placebo-controlled randomized trial of ATIII immediately after birth in intubated neonates with respiratory distress syndrome conferred no improvement in lung function and was associated with a greater mortality in the ATIII group.…”
Section: Treatment Of Coagulation Disturbancesmentioning
confidence: 99%
“…50 In children, one uncontrolled study in four patients 20 days to 17 months showed that high-dose ATIII, without heparin, was safe and effective in treating DIC and organ failure, likely through improved organ blood flow. 50 A placebo-controlled randomized trial of ATIII immediately after birth in intubated neonates with respiratory distress syndrome conferred no improvement in lung function and was associated with a greater mortality in the ATIII group. 51 Although this study was not performed on neonates with NEC, the safety issues should increase caution in proceeding with trials of ATIII in adults or neonates with sepsis or in NEC.…”
Section: Treatment Of Coagulation Disturbancesmentioning
confidence: 99%
“…These results suggest that pharmacologic concentrations of ATIII may exert a beneficial effect by mechanisms other than that currently under-stood [43]. High-dose ATIII was also reportedly useful in ameliorating organ failure in a small pediatric case series with DIC [44].…”
Section: Controversial Therapiesmentioning
confidence: 74%
“…Additionally, the efficacy of most of the drugs listed in Table II has only been demonstrated when they have been given prior to induction of experimental DIC. Notable exceptions to this statement include ATIII [42][43][44], gabexate [45,46], TFPI [56][57][58], and dithiocarbamates [62], which have been shown to ameliorate DIC in humans or experimental models after initiation of DIC.…”
Section: Novel Therapiesmentioning
confidence: 99%